Two novel lactic acid bacteria, Limosilactobacillus fermentum MN-LF23 and Lactobacillus gasseri MN-LG80, inhibited Helicobacter pylori infection in C57BL/6 mice. Issue 21 (5th October 2022) - Zhao, Yuyang; Li, Zhipeng; Zhao, Liang; Wang, Jian; Wang, Fan; Zhang, Qi; Wang, Xiaoyu; Sang, Yue; Zhan, Jing; He, Jingjing; Li, Ning; Kang, Xiaohong; et al.
Abstract : We identified two novel lactic acid bacteria Lactobacillus fermentum MN-LF23 and Lactobacillus gasseri MN-LG80 that can remarkably inhibit Helicobacter pylori infection. Abstract : Helicobacter pylori ( H. pylori ) is one of the most prevalent pathogens globally, and long-term infection causes various gastrointestinal diseases such as gastritis and even cancer. In the present study, we screened dozens of lactic acid bacteria for the efficacy to inhibit H. pylori growth in vitro, and tested the therapeutic effects of candidate strains in vivo . The results showed that Limosilactobacillus fermentum MN-LF23 (LF23) and Lactobacillus gasseri MN-LG80 (LG80) significantly reduced the abundance of Helicobacter by 90% and 83% in the infected mice, respectively, and decreased the levels of serum urease and H. pylori -specific IgG. Both bacterial strains tended to ameliorate H. pylori infection-induced gastric mucosa damage and lymphocyte infiltration, and reduced levels of serum inflammatory cytokines such as TNF-α, IL-1β, and IL-6. In addition, their culture supernatants also showed a therapeutic effect, as efficient as the bacterial cells. Furthermore, both strains significantly regulated gastric microbiota profile, and their supernatants restored the diversity of gastric microbiota. LF23 increased the abundance of Lactobacillus murinus and reduced the abundance of Desulfovibrio, whereas LG80 increased the abundance of Lactobacillus reuteri and reduced the abundance of Bilophila . Both LF23 and LG80 enriched beneficial commensals such as Faecalibaculum rodentium, and reduced detrimental bacteria such as H. pylori and Lachnoclostridium . In conclusion, we identified two novel lactic acid bacteria L. fermentum MN-LF23 and L. gasseri MN-LG80 that can remarkably inhibit H. pylori infection.